Development of physical-chemical model of forecasting of carbon in liquid pot of variable mass of arc steel-making furnace - A. G. Afanasiady (Литьë и металлургия, 2003)
There is worked out and solved the physical-chemical model of forecasting of carbon contents in furnace at production of qualitative liquid semi-product.